Kinetic Parameters during Bis-GMA and TEGDMA Monomer Polymerization by ATR-FTIR: The Influence of Photoinitiator and Light Curing Source - Aline B. Denis; Cristina A. Diagone; Ana M. G. Plepis; Rommel B. Viana (Journal of Spectroscopy)
This study aimed to analyze the kinetic parameters of two monomers using attenuated total reflectance Fourier transform infrared (ATR-FTIR): 2,2-bis-[4-(2-hydroxy-3-methacryloxypropyl-1-oxy)-phenyl] propane (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA). The following were calculated to evaluate the kinetic parameters: maximum conversion rate (Rpmax), time at the maximum polymerization rate (tmax), conversion at Rpmax, and total conversion recorded at the maximum conversion point after 300 s. Camphorquinone (CQ) and phenyl propanedione (PPD) were used in this study as photoinitiators, whereas N,N-dimethyl-p-toluidine (DMPT) amine was used as a coinitiator. LED apparatus and halogen lamp were used in turn to evaluate the effect that light source had on the monomer kinetics. The mass concentration ratio for the three resin preparations was 0.7 : 0.3 for Bis-GMA and TEGDMA: R1 (CQ + DMPT), R2 (PPD + DMPT), and R3 (PPD + CQ + DMPT). The PPD association with the CQ photoinitiator altered the polymerization kinetics compared to a resin containing only the CQ photoinitiator. The light sources exhibited no significant differences for tmax of R1 and R3. Resins containing only the PPD initiator exhibited a higher tmax than those containing only CQ. However, the Rpmax decreased for resins containing the PPD photoinitiator.